ORGANIC CULTURE OF GIANT FRESHWATER PRAWN, MACROBRACHIUM ROSENBERGII - MISHRA, R.; MISHRA, B. P.; DORA, K. C. (Journal of the Inland Fisheries Society of India, 2021)
The freshwater prawn, Macrobrachium rosenbergii, has tremendous market value. The species has great potential because of its fast growth rate, easy acceptability of both plant and animal based diets, resistance to disease and ability to withstand wide fluctuations in water quality (Durairaj et al., 1992). Monoculture of this species at stocking density above 40000 PL ha-1 is known to be more profitable as compared to polyculture (Cohen et al., 1983). Now-a-days, organic culture of fish and prawn is given much importance.